Roadblocks to Success: Examining the Resources and Performance of Micro, Small, and Medium Enterprises - Alonzo, Albert A.; Ganas, Estela S.; Abellana, Jupert Jasser G. (International Review of Management and Marketing, 2025)
This study examined the resources and performance of micro, small, and medium-sized enterprises (MSMEs) in Misamis Oriental, Philippines. Findings indicated that MSMEs effectively utilized tangible resources, particularly in inventory management and maintaining physical assets, but underutilized machinery and equipment. Although financial resources were generally well-managed, investment in human capital was notably low, revealing a significant gap in employee training and development. Intangible resources, such as brand reputation, were effectively leveraged by MSMEs, indicating their recognition of the value of maintaining a positive public image to attract customers and build loyalty. However, organizational culture, which plays a critical role in fostering employee satisfaction, collaboration, and innovation, was not fully appreciated or prioritized. On the other hand, performance analysis from 2021 to 2023 revealed sluggish recovery from COVID-19, with marginal improvements in financial and non- financial metrics. The study identified statistically significant relationships between MSME performance and all resource categories, with tangible resources exerting the most substantial positive impact. Intangible resources, while positively associated with performance, did not achieve statistical significance, suggesting their influence may manifest over longer periods or under specific conditions. The study concludes that resource utilization strategies must be optimized, particularly through investments in employee training, fostering strategic partnerships, and enhancing engagement with government programs.